Logos, Jesus en God in Johannes 1:1-5: 'n tekstuele analise - U. Busse (Acta Theologica)
In this article, the relationship between Christology and theology in John 1:1-5 is addressed. In particular, the relationship between the Logos and God has to be clarified. It is suggested that this relationship should be understood in the sense of communication between the Logos and God. This could then be interpreted further as that the Logos performed creation and the rest of God’s plans.